Gregorian chant - Hiley, David 1947- (Cambridge University Press, 2009)
What is Gregorian chant, and where does it come from? What purpose does it serve, and how did it take on the form and features which make it instantly recognizable? Designed to guide students through this key topic, this book answers these questions and many more. David Hiley describes the church services in which chant is performed, takes the reader through the church year, explains what Latin texts were used, and, taking Worcester Cathedral as an example, describes the buildings in which it was sung. The history of chant is traced from its beginnings in the early centuries of Christianity, through the Middle Ages, the revisions in the sixteenth and seventeenth centuries, and the restoration in the nineteenth and twentieth. Using numerous music examples, the book shows how chants are made and how they were notated. An indispensable guide for all those interested in the fascinating world of Gregorian chant
Keywords: Geschichte; Gregorian chants / History and criticism; Gregorianischer Gesang